Factors Influencing the Acceptance and Use of Koha Library Sofware in Academic Libraries of Uganda - Elizabeth Alikoha, Jackline Estomihi mayende, Kiwelu, andn Esther Lwanga (IJoLIS, 2024)
Purose: The study aimed at investigating factors that influence acceptance of Koha Integrated Library System(ILS) and its use in academic libraries of Uganda.